Morphological and electrical characterization of gaas nanowires - Muhammad, Rosnita (American Institute of Physics, 2009)
GaAs nanowires were grown using metal organic chemical vapor deposition (MOCVD) system at low pressure reactor chamber. The growth follows the vapor-liquid solid mechanism by applying nanoparticle gold colloid on the (111)B GaAs substrate. The growth process were done at temperatures ranging from 380 to 600°C. The prepared samples were characterized using scanning electron microscopy, SEM and conductive atomic force microscopy, CAFM. It shows that GaAs nanowires grown at lower temperatures were rod- shaped and increasingly tapered with increasing growth temperature. Electrical measurements on individual GaAs nanowires indicate ohmic characteristic for samples prepared at 440°C, while oscillation current occured for GaAs nanowire with higher growth temperatures. These properties of GaAs nanowires can be guided to provide an opportunity for direct integration of high performance III-V semiconductor nanoscale devices.